Towards safer colonoscopy: a report on the complications of 5000 diagnostic or therapeutic colonoscopies. Issue 5 (May 1983) - Macrae, F A; Tan, K G; Williams, C B
Abstract : The diagnostic and therapeutic benefits of colonoscopy are well known but most large-scale surveys, especially those involving multiple centres, may underestimate the range and incidence of complications. The detailed records of 5000 colonoscopies in a specialist unit have been analysed and conclusions drawn which may help to make the procedure safer. The incidence of haemorrhage was 1% and bowel perforation 0.1%. All the major haemorrhages occurred during polypectomies over 2 cm in size. Secondary haemorrhage was an unpredictable occurrence, one to 14 days later. Three deaths followed colonoscopy: one cardiorespiratory death was related to oversedation; a second was due to mismanaged ischaemic colitis developing two days after traumatic instrumentation, and the third was due to peritonitis. Minor complications included thrombophlebitis, abdominal distension, and vasovagal episodes. Because of experience during the first half of the series and also due to improvements in instrumentation, the complication rate of the later part of the series was halved. Recommendations include the avoidance of oversedation, review of previous barium enema films so as to be aware of large polyps which are more likely to bleed, and the recognition of situations where perforation or septicaemia is likely to occur.